Knowledge, values and skills essential for effective community development practice: A Delphi study. Issue 4 (1st October 2020) - Hains, Kristina D.; Hains, Bryan; White, Shannon; Stanard, Virginia; Rios, Michael
ABSTRACT: The field of community development has grown substantially over the past few decades. This is characterized by an increased demand for professionals who can engage in community development efforts and assist in establishing solutions. However, due to disparities within the field, there is no consistent education available for community development practitioners. To address this issue, researchers conducted a Delphi study with an expert panel of practitioners from across the United States. The panel achieved consensus on 12 knowledge constructs, 13 values, and 11 skills deemed imperative for successful community development practice. Future recommendations, implications for the field are also discussed.